DEBIT ANDALAN MODEL NRECA PADA DAS AYUNG MENDUKUNG PENGELOLAAN SEDIMENTASI DI MUARA SUNGAI - Putri, Putu Indah Dianti; Dharmayasa, I Gusti Ngurah Putu; Suryanti, Irma (Jurnal Ilmiah Teknik Sipil, 2023)
The estuary of the Ayung River often experiences sedimentation, which causes flooding in the upstream area. A good understanding of the mainstay discharge is essential in managing sedimentation in river mouths because it can help regulate optimal river water flow, identify water discharges during the rainy and dry seasons, prevent erosion and excessive sedimentation, and maintain the sustainability of ecosystems in river mouths. The NRECA method is one of the methods that can be used to estimate dependable discharge from a rain-runoff simulation model. The purpose of this study is to obtain a dependable discharge amount in the Ayung Watershed that can be used in managing river estuaries, mainly to prevent the occurrence of irregularities in the discharge of flood discharge to the sea. Water availability, as indicated by the reliable discharge in the Ayung Watershed during the wet season (Q 20% ), obtained a maximum discharge of 32.09 m 3 /second occurs in January and a minimum discharge of 7.58 m 3 /second occurs in June. Dry season conditions (Q 80% ) obtained a maximum discharge of 10.76 m 3 /second occurs in January and a minimum discharge of 0.68 m 3 /second occurs in June. Meanwhile, normal conditions (Q 50% ), a maximum discharge of 22.84 m 3 /sec occurs in January and a minimum discharge of 1.74 m 3 /second occurs in August.